Effect of Social Media on Patient’s Perception of Dental Aesthetics in Saudi Arabia - Khadijah M. Baik; Ghazal Anbar; Abeer Alshaikh; Arwa Banjar (International Journal of Dentistry)
Introduction. Social media became an influential tool that affects people’s way of communication and became a significant source of information for the society. The study aimed to evaluate the impact of SM on patients seeking aesthetic dental treatment. Methodology. The study employed a large-scale online survey of 1940 patients attending and/or seeking dental treatment at KAUFD and Jeddah private clinics. The targeted age of participants ranged from 18 years and above. The study data were collected using a three-part questionnaire. Results. More than half of the patients were females in both groups (52.7%). The majority of patients used SM for communication and entertainment purposes. It was also found that the most popular platform used by patients was Snapchat (71.1%), followed by Instagram (66.9%). A lot of patients did not like their teeth appearance (38.5%). Moreover, patients preferred to have “bleaching” as an aesthetic treatment to improve their smiles (63.8%). Conclusion. The impact of SM on Saudi Arabian citizens and Saudi Arabia residents can be considered as high. Patients are influenced by SM applications and are seeking aesthetic treatment as an outcome. It is the responsibility of dentists to educate patients about the best treatment options.